Avaliação da remoção de pesticidas em vinho branco por membranas de microfiltração - Turella, Taís Caroline (My University, 2021)
The use of pesticides in agriculture is the subject of discussions due to the dangers generated for the environment and for human health. However, crop protection with chemical methods is a common practice in viticulture, due to the specificities of the grape culture, its diseases and pests. The number of pesticides, type and quantity applied to the vines varies significantly each year, depending on climatic conditions, growth of pests, incorrect application of the producer, etc. Therefore, pesticide residues are often detected in grapes and wine. In order to develop an alternative for the removal of pesticides in wines, this work evaluated the retention of the pesticide carbendazim and indoxacarb by microfiltration (MF) with polymeric membranes in white wine. The quality of the final product after MF was also evaluated through physical-chemical analyzes. The tested membranes were 0.45 μm cellulose acetate (CA). The modified QuEChERS (Quick Easy Cheap Effective Rugged Safe) extraction method followed by direct infusion in high resolution mass spectrometry (DI-HRMS) and liquid chromatography coupled with high resolution mass spectrometry (HPLC-HRMS) were performed for analysis of pesticide residues from microfiltered fortified wine. The spectra obtained showed that the membrane showed a potential for pesticide retention after microfiltration, regardless of the concentration used in the fortification. The use of MF also preserved the quality of the wine, as it showed no changes in its physical and chemical characteristics after the process. Therefore, the use of MF polymeric membranes presents itself as a promising alternative in the removal of carbendazim and indoxacarb residues that may be present in wines. [resumo fornecido pelo autor]
O uso de pesticidas na agricultura é tema de discussões em virtude dos perigos gerados para o meio ambiente e para a saúde humana. No entanto, a proteção das culturas com métodos químicos é uma prática comum na viticultura, devido às especificidades da cultura da uva, doenças e pragas que acometem as videiras. O número de pesticidas, tipo e quantidade aplicados nas videiras variam significativamente a cada ano, dependendo das condições climáticas, crescimento de pragas, aplicação incorreta do produtor, etc. Por isso, resíduos de pesticidas são frequentemente detectados nas uvas e no vinho. Com o objetivo de desenvolver uma alternativa para a remoção de pesticidas em vinhos, este trabalho avaliou a retenção do pesticida carbendazim e indoxacarbe por microfiltração (MF) com membranas poliméricas em vinho branco. Também se avaliou a qualidade do produto final após a MF a partir de análises físico-químicas, tais como álcool, turbidez, açucares, entre outros. As membranas testadas foram de acetato de celulose (CA) de 0,45 μm. O método de extração modificado QuEChERS ( do inglês Quick Easy Cheap Effective Rugged Safe) seguido de infusão direta em espectrometria de massa de alta resolução (DI-HRMS) e cromatografia líquida acoplada a espectrometria de massa de alta resolução (liquid chromatography coupled with high resolution mass spectrometry, HPLC-HRMS) foram realizados para analisar resíduos de pesticidas do vinho fortificado (denominação dada ao vinho no qual foram adicionadas concentrações de pesticidas) microfiltrado. Os espectros obtidos evidenciaram que a membrana apresentou um potencial de retenção de 46 % de carbendazim e 65% de indoxacarbe após MF. Este processo preservou a qualidade do vinho, pois o mesmo não apresentou alterações em suas características físico-químicas após a MF. Portanto, a utilização de membranas poliméricas de MF se apresenta como uma alternativa promissora na remoção de resíduos de carbendazim e indoxacarbe que possam estar presentes em vinhos. [resumo fornecido pelo autor]
Keywords: Filtração por membranas; Vinho; Pesticidas; Membrane filtration; Wine; Pesticides